The Effect of Growth Regulator Substance on Shoot Cutting of Jamblang (Syzygium cumini (L.) Skeels - Aris Sudomo; Maman Turjaman (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2018)
Development of jamblang (Syzygium cumini) as medicinal plant currently constrained by the aspects of cultivation technology (vegetative propagation), so the provision of medicinal plants for the mass scale was very difficult. The objective of this research was to evaluate the effect of five doses of growth regulator substance on growth of S. cumini’s shoot cuttings. The active ingredient composition of hormone/ Growth Regulator Substance (GRS) in this study were Naphthalene Acetic Acid (NAA) 3 percent and Naphthalene Acetamide (NAAm) 0.75percent. The experiment was arranged in Completely Random Design using 5 concentrations of growth regulator substance namely 0g.10ml-1(control), 2g.10 ml-1, 4g.10ml-1, 10g.10ml-1 and powder (not dissolved). The results of this experiment proved that 4g.10 ml-1of growth regulator substance produce the highest height growth (29.84 cm or 21.74 percent increment), the highest number of leaves (23.72 pieces or 4.63 percent increment), the heaviest dry weight of stem and leaves (3.36 gram or 43.59 percent increment) and the highest top-root ratio (6.55 or 10.08 percent increment). The highest survival percentage was resulted from GRS powder treatment (80 percent or 18.81 percent increment), but did not significantly different to GRS treatment of 4g.10 ml-1 (77.33 percent). The application of 4g.10 ml-1 is recommended to use to produce the better growth of cuttings planted on soil.